Smoke Signals Selected Writing - Chapman, Simon (Sydney University Press, 2016)
Smoke Signals gathers 71 of Professor Simon Chapman's authoritative, acerbic and often heretical essays from across his 40-year career. They cover major developments and debates in tobacco control, public health ethics, cancer screening, gun control, and panics about low risk agents such as wi-fi, mobile phone towers and wind turbines. This collection is an essential guide to many key debates in contemporary public health. It will be invaluable to public health students and practitioners, and provides compelling, entertaining reading for anyone interested in health policy.